KONTRUKSI PEMIKIRAN PENDIDIKAN ISLAM MENURUT ABDUL MALIK FADJAR - Khoulita, Ikfi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Islamic education is the process of fostering, nurturing and teaching students, so that they can always understand and know Islam as a whole and practice it and teach it, meaning that Islamic education aims to produce generations of Muslims who always believe and fear God and have good morals and are able and skilled in social life. Abdul Malik Fadjar's general thinking shows that Islamic education thinking must show fundamental changes and improvements in the system and management of Islamic education to achieve quality education goals that can mobilize all educational resources, which are taken from Abdul Mallik Fadjar's thinking. Based on the results of the study, the values contained in Islamic education according to Abdul Malik Fadjar are to form students to develop as a generation of khaih ummah, faith and devotion, mature in attitude, have independent thinking and spirit, creative, dynamic and noble character.